Thermal Degradation and Water Uptake of Biodegradable Resin Prepared from Millet Flour and Wheat Gluten Crosslinked with Epoxydized Vegetable Oils - Abdellatif A. Mohamed; S. Hussain; M. S. Alamri; M. A. Ibraheem; Akram A. Abdo Qasem (Journal of Chemistry)
The degradation temperatures (DTs), heat stability (IPDT), degradation kinetics, and water uptake of epoxy resin were investigated using thermogravimetric analysis. Epoxy resins were prepared by crosslinking epoxydized oils with vital wheat gluten (VG) and millet flour. The reactions included three oils (cottonseed, sesame, and sunflower) and three levels of zinc chloride (ZC) (1, 2, and 3%). The apparent activation energy (Ea) was calculated using the Flynn–Wall–Ozawa method. The DT increased at higher heating rates within the same ZC level of the same oil type. Cottonseed oil exhibited the highest DT. The highest IPDT was 637°C of the sunflower oil/millet resin (3% ZC), and the least was the cottonseed/millet (1% ZC) at 479°C. The sesame-millet resin exhibited the highest Ea (622 KJ/mol) followed by sunflower-gluten (496 KJ/mol) and sesame-gluten (454 KJ/mol). The profiles of all resins point to a multistep degradation, but some of the profiles display two dominant kinetic processes, and the remaining resins showed three processes. The variation in crosslinking density between the oils is attributable to the different amounts of oxirane rings which are associated with the double bonds of the fatty acid of the oils. Like other parameters, the water uptake was affected by the ZC content, where most of the resins did not reach water uptake equilibrium. Nonetheless, the 3% ZC resin reached equilibrium after 5 days of immersion.